Taking Action on Usability Testing Findings: Simmons College Library Case Study. Issue 3 (16th November 2016) - Clark, Andrew R.; Erdmann, Annie; Ferguson, Jennifer; Gambrell, Khalilah; Shaw-Munderback, Jeremy B.
ABSTRACT: Simmons College Library conducted in-person and remote usability testing to observe how students retrieve full text when using Library Search, its discovery service system powered by EBSCO Discovery Service (EDS). Testing was conducted as a collaborative study with a consultant associated with EBSCO Information Services User Research Group. This testing found that students expect direct access to full text, have an unfavorable impression of Interlibrary Loan (ILL), and are unsure, based on terminology, which links provide direct access to full text. Steps taken by the library in response to the findings include local customization of EDS, improvements to ILL messaging, updates to user education regarding full text formats and terminology, and requests to EBSCO to update terminology to support users' direct access to full text. Study findings also validated decisions the library made during the initial set up of its discovery service system.